2001
DOI: 10.1051/0004-6361:20010196
|View full text |Cite
|
Sign up to set email alerts
|

Photometric and kinematic studies of open star clusters

Abstract: Abstract. We present CCD photometry and proper motion studies of the three open star clusters NGC 4103, NGC 5281, and NGC 4755 (κ Cru). By fitting isochrones to the colour magnitude diagrams, we found that all three objects are young open star clusters with ages of at most t = 45 Myr. They are located at distances from approx. 1600 pc to 2200 pc, derived from distance moduli (m−M )0 ranging from 11 mag to 12 mag. We combined membership determinations based on proper motions and statistical field star subtracti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(136 citation statements)
references
References 35 publications
(52 reference statements)
11
120
5
Order By: Relevance
“…The almost 3σ discrepancy between the cluster's proper motion results obtained by this work, D06, and Sanner et al (2000), may be caused by the different materializations of the HIPPARCOS reference system. As for UCAC2, PM2000 is linked to HIPPARCOS as materialized by Tycho-2.…”
Section: Ngc 2194contrasting
confidence: 56%
See 2 more Smart Citations
“…The almost 3σ discrepancy between the cluster's proper motion results obtained by this work, D06, and Sanner et al (2000), may be caused by the different materializations of the HIPPARCOS reference system. As for UCAC2, PM2000 is linked to HIPPARCOS as materialized by Tycho-2.…”
Section: Ngc 2194contrasting
confidence: 56%
“…NGC 2194 is an open cluster located in a moderately rich field projected along the Galactic anti-centre direction, which has been studied by Kyeong et al (2005), Piatti et al (2003), and Sanner et al (2000). Only the final of these three aforementioned studies deals with proper motions.…”
Section: Ngc 2194mentioning
confidence: 99%
See 1 more Smart Citation
“…Feast (1963) 0 .48 ± 0.01 11.86 ± 0.14 2360 · · · Kennedy (1966) 0.46 11.9 Becker & Fenkart (1971) 0.31 Perry et al (1976) 0 .40 ± 0.01 11.8 ± 0.2 · · · 7 Shobbrook (1984) 0 . 3 8 1 1 .4 ± 0.1 Sanner et al (2001) 0 .36 ± 0.02 11.6 ± 0.2 2100 ± 200 10 ± 5 McSwain & Gies (2005) 0.38 11.80 2290 7 This work 0.30 12.10 ± 0.39 2630 ± 475 11…”
Section: (B8 V)mentioning
confidence: 84%
“…The slope is Γ ∼ 1.3 − 1.4 out to stellar masses greater than 100 M ⊙ (Massey & Hunter 1998). In addition, h and χ Persei (Slesnick, Hillenbrand & Massey 2002), NGC 604 in M33 (González Delgado & Pérez 2000), NGC 1960 and NGC 2194 (Sanner et al 2000), NGC 6611 (Belikov et al 2000) and many other clusters have Salpeter IMFs (e.g., Sakhibov & Smirnov 2000;Sagar, Munari, & de Boer 2001). Massey & Hunter (1998) concluded that the Salpeter IMF occurs in star-forming regions spanning a factor of 200 in density.…”
Section: Clustersmentioning
confidence: 99%